2002
DOI: 10.1542/peds.109.5.780
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Ketogenic Diet for Infantile Spasms

Abstract: The ketogenic diet is a safe, well-tolerated, and possibly effective potential alternative to other therapies for infantile spasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
128
2
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(145 citation statements)
references
References 25 publications
9
128
2
4
Order By: Relevance
“…Class 4 evidence supports the role of the ketogenic diet for infants younger than 1 year of age, and class 3 evidence for children aged 12-24 months. [12][13][14][15][16][17][18][19][20] There is evidence that ketosis can be sustained in infants.…”
Section: Approach To Therapy and Interventions In Infantile-onset Seimentioning
confidence: 99%
“…Class 4 evidence supports the role of the ketogenic diet for infants younger than 1 year of age, and class 3 evidence for children aged 12-24 months. [12][13][14][15][16][17][18][19][20] There is evidence that ketosis can be sustained in infants.…”
Section: Approach To Therapy and Interventions In Infantile-onset Seimentioning
confidence: 99%
“…Response to the diet was maintained for at least 6 months in seven of the 10 responders and for at least 1 year in two patients. In two patients with cryptogenic epilepsy, the ketogenic diet was stopped after 6 and 11 months of seizure freedom (7,11), but the epilepsy subsequently relapsed after 2 and 9 months respectively. The reintroduction of the diet controlled seizures again for one of them.…”
Section: Results (mentioning
confidence: 99%
“…1,2 Many investigators have confirmed the benefits that this treatment can offer to young patients with epilepsy, [3][4][5][6] including infants. 7,8 However, the best indications for using the diet have not been clearly defined since it was shown to be helpful in treating a large range of different seizure types and epilepsy syndromes. Special interest has been given to various conditions associated with epilepsy including myoclonic astatic epilepsy, 5,9 infantile spasms, 7 Dravet syndrome, 10 atypical absences, 11 acquired epileptic aphasia, 12 tuberous sclerosis, 13 and Rett syndrome.…”
mentioning
confidence: 99%
“…10,17 Treatment of infantile spasms with steroids, different AEDs, or ketogenic diet is rarely effective. [18][19][20][21] Even though therapeutic procedures in congenital CMV infection have yet to be established, 22,23 using an antiviral regimen in epilepsy caused by congenital HCMV infection was considered. Only one case report from Greece concerning unsuccessful treatment with GCV of a patient with infantile spasms caused by HCMV infection has been published so far.…”
Section: Discussionmentioning
confidence: 99%